Kesenjangan Normatif-Empiris Implementasi Kurikulum Merdeka: Analisis Kritis Integrasi Nilai Islam dan Profil Pelajar Pancasila di SMP IT Al-Amanah Ciamis - Muhammad Sholeh Afif; Fatnun Fajriyah; Putri Ulia Rahma; Ni'matul Mahmudah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Previous studies indicate that the implementation of the Merdeka Curriculum continues to exhibit disparities between policy design and educational practice across schools. These challenges are more pronounced in Integrated Islamic Schools located in rural areas, where the national curriculum must be aligned with institutional characteristics, religious values, and limited educational resources. Despite this context, comprehensive studies examining the interrelationship among curriculum philosophy, curriculum structure, instructional practices, assessment, the Projek Penguatan Profil Pelajar Pancasila (P5), and institutional capacity remain limited. This study aims to analyze the implementation of the Merdeka Curriculum at SMP IT Al-Amanah, Ciamis Regency, by examining the alignment between curriculum design and its implementation in educational practice. A qualitative approach with a case study design was employed. Data were obtained from the 2025/2026 School-Based Curriculum (Kurikulum Satuan Pendidikan), supported by a literature review. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, while source triangulation was employed to enhance the credibility of the findings. The findings reveal that the Merdeka Curriculum has been implemented through intraclass learning, the Projek Penguatan Profil Pelajar Pancasila (P5), assessment based on the Learning Objective Achievement Criteria (Kriteria Ketercapaian Tujuan Pembelajaran [KKTP]), and the integration of Fiqh as a subject reinforcing the school's Islamic identity. The curriculum's flexibility provides opportunities to adapt learning to students' characteristics and the local context. However, its effectiveness is still influenced by teachers' pedagogical capacity, limited learning facilities, and institutional support. These findings suggest that optimizing the implementation of the Merdeka Curriculum requires strengthening teachers' professional competence, improving educational infrastructure, and promoting adaptive and sustainable school governance.